Female social response to male sexual harassment in poeciliid fish: a comparison of six species - Dadda, Marco (Frontiers in Psychology, 2015)
Sexual harassment is common among poeciliid fish. In some fishes, males show a high frequency of sneak copulation; such sexual activity is costly to the females in terms of foraging efficiency. In mosquitofish (Gambusia holbrooki), when males are present, the distance between females tends to decrease, and this behavior has been interpreted as an adaptive strategy to dilute the costs of male sexual activity. In this study, the tendency to reduce distance in the presence of a male has been investigated in females of six poeciliid species (Girardinus metallicus, Girardinus falcatus, G. holbrooki, Poecilia reticulata, Xiphophorus hellerii, and Xiphophorus mayae) that exhibit different male mating strategies and different levels of sexual activity. Results revealed large interspecific differences in the pattern of female aggregation. Females of species with a high frequency of sneak copulations tended to reduce their social distance in the presence of a male. By contrast, species that rely mainly on courtship showed little or no variation in social distance. The proportion of sneak copulations predicts the degree of variation in female social response, but the amount of total sexual activity does not, suggesting that the change in females' social distance when a male is present may indeed serve to reduce the costs of male sexual harassment.